Preparation, characterization and optimization of biochar from oil palm empty fruit bunch - Mansor, Nur Fatin Amira (2020)
Fossil fuel supply is limited and they will be depleted one day. Alternative fuels such as hydrogen and biomass are essential and play a huge role together with the natural gas in the changeover to renewable energies. In this study, the production of biofuels from Oil Palm Empty Fruit Bunches (OPEFB) has been used to identify the potential of pyrolysis biochar as a renewable energy source through thermochemical routes. The biochar was produced using a furnace at holding temperatures of 400, 500 and 600 oC and residence time at 15, 30 and 45 minutes. This research focused on the analysis of mass yield and optimization using surface response methodology (RSM), the Box-Behnken Model and the analysis of the bonding behaviour of pyrolysis OPEFB biochar due to its properties and functional groups. The raw OPEFB and product (biochar) were characterized usingFourier transform infrared spectroscopy (FTIR) to find the functional groups. The optimum conditions suggested by Design Expert 7.1.6 are at 662.50 μm of particle size,401.67 °C of holding temperature and 19.25 min of residence time with 90.6632 % mass yield in order to obtain the most efficient OPEFB biochar. Whereas, the actual experiment showed a mass yield of 92.64 % which indicates an excellent match for values of biochar in predicted and experimental results.